Integrasi Wanamina Dalam Perikanan: Pendekatan Komprehensif Untuk Konservasi Mangrove - Rozikin, Iftisar; *, Apriyadi (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Mangroves are important ecosystems that provide a variety of ecosystem services, but are threatened by deforestation and land conversion. The integration of wanamina, a coastal agroforestry system that combines fish cultivation with mangrove conservation, is proposed as a potential solution. This research uses a qualitative approach with case study methods from Indonesia, the Philippines and Bangladesh to evaluate the implementation of wanamina. The results show that the integration of agroforestry can increase fisheries productivity and maintain the function of the mangrove ecosystem. In Indonesia, fishermen's income increased by 20% and deforestation was reduced by 15%. In the Philippines, shrimp production increased 25% and mangrove biodiversity increased. In Bangladesh, pressure on mangrove ecosystems is reduced and community welfare is increased. The success of agroforestry depends on government policy, community participation, knowledge and local ecological conditions. Wanamina has great potential as a model for sustainable coastal resource management